2018
DOI: 10.4236/ojss.2018.810020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trichoderma koningiopsis on Chickpea Rhizosphere Activities under Different Fertilization Regimes

Abstract: Interaction of plant growth promoting microorganisms (PGPMs) with plants involves interplay at physical, physiological and molecular levels. Proliferation and root colonization of PGPMs manipulate the rhizosphere to optimize plant functions. This benefits plant by nutrient enrichment and induction of plant vigor and defense system. The present work aims to decipher the rhizosphere modulations promoted under different fertilization regimes by an organic acid producing Trichoderma koningiopsis strain (NBRI-PR5).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 34 publications
(34 reference statements)
1
4
0
Order By: Relevance
“…Alkaline phosphatase, but not acid phosphatase, is mainly associated with microorganisms, so an increase in microbial biomass conferred the observed higher alkaline phosphatase activity. The enhanced decomposition of organic matter, especially with the action of inoculated fungi, appeared a regulatory influence on the alkaline phosphatase activity matching the findings of Tandon et al (2018) for microbial activities in rhizosphere of chickpea inoculated with Trichoderma koningiopsis under dissimilar fertilization treatments.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Alkaline phosphatase, but not acid phosphatase, is mainly associated with microorganisms, so an increase in microbial biomass conferred the observed higher alkaline phosphatase activity. The enhanced decomposition of organic matter, especially with the action of inoculated fungi, appeared a regulatory influence on the alkaline phosphatase activity matching the findings of Tandon et al (2018) for microbial activities in rhizosphere of chickpea inoculated with Trichoderma koningiopsis under dissimilar fertilization treatments.…”
Section: Discussionsupporting
confidence: 77%
“…They suggested that inoculated organic fertilizer with Trichoderma is a better option for maintaining a relatively sustainable microbiome in mono-cropped soils under a 25% reduction of inorganic fertilizer. Also, Tandon et al (2018) attributed the inhibitory effect of 100%-NPK chemical fertilizers comparing 50%-NPK on bacterial CFU of microflora in chickpea rhizosphere to lowering soil pH and exert destructive effects caused by mineral fertilizers.…”
Section: Discussionmentioning
confidence: 99%
“…phosphate -Tandon et al, 2018) and is more efficient and competitive that many other fungi. In consequence, it can therefore be used effectively to improve the soil structure and promote the establishment and maintenance of other beneficial microorganisms (Benitez et al, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…Diánez et al [16] described a highly similar IAA production for T. saturnisporum; therefore, the in vitro production capacity of IAA was preserved despite maintaining the isolate in the laboratory for 10 years. Similarly, phosphate solubilisation by Trichoderma species has been described both in vitro and in vivo [52][53][54]. Recently, Tandon et al [55] evaluated P solubilisation of different Trichoderma koningiopsis isolates under abiotic stress conditions and determined a range from 1.6 to 71 µg mL −1 .…”
Section: Discussionmentioning
confidence: 99%